Value Determinants, Mentality and Identity of the Bosnian-Herzegovinian Village at the Beginning of the 20th Century according to Ivan Softa’s Literary Works - Tomić , Draženko; Legac , Vladimir (Acta humanitarica academiae Saulensis, 2022)
Ivan Softa (Sopta) (1906–1945) was a Croatian writer from Bosnia and Herzegovina. In his realistic novels Dani jada i glada (Days of Misery and Hunger) (1937) and Nemirni mir (Restless Peace) (1940), as well as in his other literary achievements, he describes the life of the Herzegovinian village at the time when the First World War was about to start. It was an ambience dominated by bare stone, hot sun, sharp north wind called bora, with somewhat scarce and sparse land that made an easy life impossible. These resources that abound in this Western Balkans region also shaped the specific (Dinaric) mentality of the people of that time: hard as the stone on which they grew up, aggressive and easily flammable like the sun that they were exposed to and unrestrained like the wind, the whipping of which they mercilessly suffered from. But it happened that even from that fiery temper some kind of an original mountaineering-like honesty and confidence, empathy and readiness for self-sacrifice had emerged. Personal martyrdom turning into self-destruction – something that seems to be completely inconceivable to modern man – is embodied in the female characters, whereas emotional rawness and hardness are more characteristic of the author’s male characters. The tragic circumstances of war and famine caused emigration to regions where there was bread. These tragic circumstances resulted in the tragic fate of the characters who left the Herzegovinian environment and, like many others, fell apart on the side roads of life.
Keywords: World War One (Bosnia-Herzegovina); mentality of the Herzegovinian village at the beginning of the 20th century; amine in Herzegovina during the First World War; the Great Depression (1929–1933)